The meteorite collection of the Museo Nazionale dell’Antartide in Siena - FOLCO, LUIGI; Rastelli N. (2000)
The catalogue for the meteorite collection of Siena's Museo Nazionale dell'Antartide is presented. The collection primarily contains meteorites recovered from the Antarctic by the Italian National Programme for Antarctic Research but also includes specimens from various locations around the world. To date (April 2000), the collection totals 722 specimens. Of these, 533 specimens are classified, including 500 chondrites, 21 achondrites, 3 stony-iron meteorites, and 9 iron meteorites.